A Critical Review of the Book “Scientific Research; Bases, Methods and Principles, Procedures” - Sadeq Askari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critical analysis of scientific productions highlights the strengths and weaknesses of authors and avoids the weaknesses. Achieving the desired perfection in the compilation of academic resources is possible after explicit and constructive criticism. In this article, “Scientific Research, Its Foundations, Methods and Principles, Procedures”, written by Mostafa Robhi Alianhas, been criticized. The results of the critique and review of this book show that this book, despite some strengths such as the use of many and varied sources, the use of exercises and tables and diagrams that have played an effective role in explaining and teaching concepts, however, have many defects in the field of form and content, unfortunately. The most important formal defects include lack of strict observance of general rules of writing, interpretive and syntactic errors due to incorrect use of words and combinations, lack of formal comprehensiveness due to lack of introduction and methodical conclusion. The most important content shortcomings include repetition of the subject, incomplete arrangement and chaptering, superficial and hasty review, reliance on compilation and collection, and as a result, lack of critique and innovation.